Effects of Melia azedarach L. leaf and fruit on mineralization of carbon in soil (Bangladesh Journal of Botany, 2014)
Carbon mineralization in soil increased significantly due to additions of pure azadirachtin and powdered leaves and fruits of Melia azedarach L. under in vitro incubation for 30 days at 28°C. Cumulative respired C(CO2) clearly increased with incubation time in all treatments except in soil mixed with pure azadirachtin (p < 0.001). Carbon mineralization ratio in soils mixed with single doses of powdered leaf and fruit were significantly higher than the other doses tested.